2018
DOI: 10.1111/jce.13711
|View full text |Cite
|
Sign up to set email alerts
|

Cessation of pacing in super‐responders of cardiac resynchronization therapy: A randomized controlled trial

Abstract: LVEF was significantly reduced in super-responders of CRT 6 months after cessation of pacing. Super-responders to CRT should receive continued, long-term pacing to preserve recovered LV function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Liang et al demonstrated that even super-responders sometimes exhibited a recurrence of electrical and mechanical remodeling after CRT discontinuation [ 5 ]; therefore, CRT should be continued when possible to promote these protective factors. In our patient, CRT was discontinued because of the high rate of battery consumption; however, this was a special case, and current evidence and guidelines do not recommend the discontinuation of CRT.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Liang et al demonstrated that even super-responders sometimes exhibited a recurrence of electrical and mechanical remodeling after CRT discontinuation [ 5 ]; therefore, CRT should be continued when possible to promote these protective factors. In our patient, CRT was discontinued because of the high rate of battery consumption; however, this was a special case, and current evidence and guidelines do not recommend the discontinuation of CRT.…”
Section: Discussionmentioning
confidence: 99%
“…However, because of limited data, we cannot elucidate the mechanisms involved. Many studies and guidelines have recommended that CRT should be continued as long as possible [ 5 , 6 , 19 ] and discontinuation is not recommended. In this case, although CRT was discontinued, good results were achieved, and HF did not recur.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, while symptom improvement was the standard measure for most studies, there were patients who were "super responders" who actually developed improvement in their left ventricular ejection fraction after CRT, and it is difficult to predict which patients might receive this advantage. 5 As the data increasingly have shown that patients with LBBB are more likely to benefit from CRT compared to right bundle branch block or non-specific intraventricular conduction delays, most society guidelines require a true LBBB to meet a class I indication for CRT. 6,7 The difficulty with using LBBB as a metric for CRT candidacy is that defining it has been controversial.…”
mentioning
confidence: 99%